Relasi antara Kepercayaan dan Hunian Masyarakat Jawa di Kediri Jawa Timur - Meylinda Meylinda; Lintu Tulistyantoro; Filipus Priyo Suprobo (Intra, 2018)
Kediri is a city affected by mataraman culture. It can be observed from the kejawen belief that is still embraced by the Java community in Kediri, for example is the people who live in the village of Sumberbendo, Semanding, and Pehwetan. Kejawen belief is closely related to the concept of macapat mancalima, there is always be a central which coordinate everything. The main goal of this belief is to get the balance. Kejawen's beliefs become a cornerstone of life for the Javanese who live in these villages. Trust is also expressed through their occupancy, for example in terms of space organization, residential expansion, zoning, and also the hierarchy of space (sacred-profane). The research method used is descriptive qualitative research with ethnography approach. This study were taken ten samples consisting of three districts in Kediri namely, district Pare (Sumberbendo Village), Pagu (Semanding Village), and Papar (Pehwetan Village). There is a strong relationship between the beliefs and the dwelling of Javanese community in Kediri East Java, especially in the three villages that become the research sample. Embodied through ritual activity and life cycle that occurs in the omah. All rituals carried out by Sumberbendo, Semanding, and Pehwetan communities are closely related to obtaining salvation and tranquility which means the balance between man and God, man with nature, man with other human beings, and man with himself. Omah is a container to perform these four principles of trust.